Integrating Islamic Human Resource Management and Digital Communication to Foster Ethical Business Practices in Multinational Corporations - Agus Supriyanto (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, Institut Agama Islam Sunan Giri Ponorogo, 2025)
The rapid growth of digital entrepreneurship has transformed multinational corporations (MNCs), creating new ethical challenges in human resource management, including digital surveillance, blurred work–life boundaries, and employee burnout. This study explores how the integration of Islamic Human Resource Management (IHRM) and Digital Internal Communication (DIC) contributes to the development of ethical business practices in digital MNCs. A qualitative exploratory case study approach was employed in a digital technology multinational company operating across Southeast Asia. Data were collected through semi-structured interviews with 12 informants, including HR managers, senior executives, and digital professionals. The data were analyzed using manual thematic analysis following Braun and Clarke’s six-stage framework. The findings reveal three major themes: (1) the manifestation of 'adl (justice) through transparent digital communication and performance evaluation systems; (2) the reinforcement of amanah (accountability) through trust-based management in Work-From-Anywhere environments; and (3) the reduction of technostress through the implementation of ihsan (benevolence) via employee well-being initiatives, including the Right to Disconnect policy. The study demonstrates that integrating IHRM principles with digital communication practices can foster a more ethical, human-centered, and sustainable organizational environment in multinational digital enterprises.